Pengaruh Job Burnout, Stres Kerja dan Motivasi Kerja terhadap Turnover Intention Financial Future Indonesia - Dwiyanti, Irma; Natasya Ayu Afriadi, Kania; Annisa, Muthi Rizky; Lathiifanindia; Mulyadi, Mulyadi (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to find out how work stress, work motivation, and loss of motivation impact the desire to leave work. This research method involves the use of quantitative methods, descriptive approaches, and SPSS 24 tools for Windows. This study use a non-probability saturated sample method with 30 employees from Financial Future Indonesia. The result show that the level of fatigue, work stress, and work motivation partially affect the desire to leave work.